The effects of LMNA mutations causing dilated cardiomyopathy on nuclear structure and cell survival under mechanical stress - Mattila, Sini (My University, 2024)
Lamin A and C, encoded by the LMNA-gene, are intermediate filament proteins expressed in nearly all human tissues. LMNA gene mutations are known to cause a diverse group of diseases referred to as laminopathies. The most common laminopathy is dilated cardiomyopathy (DCM), which causes ventricular dilatation, conduction defects, and potentially sudden cardiac death. Although multiple hypotheses have been proposed to explain the pathogenesis of laminopathies, the exact mechanism remains elusive. This review focuses on the mechanotransduction hypothesis, which suggests mutant lamin proteins cause disrupted mechanotransduction and altered downstream gene regulation and mechanosensing. Mechanotransduction can be simplified as a process of translating mechanical forces into biological responses. Based on the current publications, the researchers are unanimous that LMNA mutations cause disrupted nuclear structure and cell signaling. LMNA mutations have been recognized to significantly alter the nuclear architecture, protein binding, gene transcription, localization, and stability of the transcription factors. The main abnormalities described in research literature are nuclear defects and signaling aberrations. Nuclear alterations associated with LMNA-DCM are nuclear ruptures, softer and elongated nuclei, nuclear lobulations, loss of peripheral heterochromatin, and aberrant nuclear pore complex distribution. Striated muscle laminopathy mutations have been reported to result in abnormal activation of the signaling proteins ERK, JNK, p38α, mTOR, and Akt. The identified abnormalities have been examined in multiple research set-ups with LMNA mutant cells and mouse models. The research suggests that continued mechanical stress, such as excessive training or cell stretching, increases nuclear aberrations but does not necessarily compromise viability of cells in vitro or survival of Lmna-mutant mice. These results support the theory of haploinsufficiency and abnormal mechanotransduction as a probable part of the DCM pathogenesis.
Keywords: lamin A/C, LMNA, dilated cardiomyopathy, mechanotransduction